Computer-based laboratory exercises: Assessing lab practice preferences among computer engineering's students and lecturers - Saod, Aini Hafizah Mohd; Harron, Nur Athiqah; Ramlan, Siti Azura; Sadimain, Shahidah; Razak, Faridah Abdul (2016 IEEE 8th International Conference on Engineering Education (ICEED), 2016)
This study is proposed to determine lab practice preferences for computer-based laboratory exercises. A quantitative data is collected through survey questionnaires among computer engineering's students and lecturers of Universiti Teknologi MARA Pulau Pinang. The survey items focus on four aspects; which are lab conduction, lab assessment, lab report writing and submission. A total of 87 correspondents have taken part in the survey. The findings of the survey indicate that they are preferred to use a computer-based tools system in conduction of computer-based laboratory exercises.